Physico-chemical features of aluminum hydroxides as modeled with 2 the hybrid B3LYP functional and localized basis functions - Demichelis, Raffaella; Noel, Y.; Ugliengo, P.; Zicovich-Wilson, C.; Dovesi, R. (American Chemical Society, 2011)
Aluminum hydroxides (a family of seven compounds) are key raw materials in the aluminum industry, and indeed an extremely large variety of experiments and simulations was performed in the last 50 years on this class of materials. However, many of their properties still remain a matter of debate, as a comprehensive and comparative analysis of the full family is still lacking. Some of the open questions related to their structure (space group definition, H order-disorder), energetics (relative stability with respect to each other and to the dehydrated phase), and vibrational spectrum (broad bands in the OH stretching region causing large differences in the interpretation of the experimental IR and Raman spectra by the various authors) are addressed in this work with a quantum mechanical ab initio approach, using the CRYSTAL09 periodic code, a rich all-electron Gaussian type basis set, and the hybrid B3LYP functional. This review presents the first complete, systematic, and homogeneous (same method, computational parameters, basis set, and Hamiltonian) investigation of the crystal structure, energetics, and vibrational spectra of this family of compounds, showing that quantum mechanical simulation is likely to provide complementary data for their complete characterization